INFLUENCE OF TRANSCRIPTION FACTOR ΚB ON REMODELING OF EXTRACELLULAR MATRIX OF RAT LIVER UNDER CONDITIONS OF CHRONIC ALCOHOL INTOXICATION - Mykytenko, A.O.; Akimov, O.Ye.; Yeroshenko, G.A.; Neporada, K.S. (World of Medicine and Biology, 2022)
Liver fibrosis is a common tissue reaction associated with chronic liver damage resulting from prolonged parenchymal cell damage and inflammation. The fibrogenic response is characterized by the progressive accumulation of extracellular matrix components enriched in collagen fibrils and impaired extracellular matrix remodeling. The aim of this study was to establish the effect of transcriptional factor κB on the concentration of oxyproline, glycosaminoglycans and sialic acids in the liver of rats under conditions of chronic alcohol intoxication. The study was performed on 24 male Wistar rats. The animals were divided into 4 groups of 6 animals: І – control; II – animals with inhibition of κB; ІІI – animals with chronic alcohol hepatitis and ІV – animals with κB inhibition on the background of chronic alcohol intoxication. We studied the total concentration of glycosaminoglycans, concentration of heparin-heparan, keratan-dermatan and chondroitin fractions of glycosaminoglycans, free oxyproline and sialic acids in the liver tissue homogenate. Prolonged alcohol intoxication of rats leads to remodeling of the extracellular matrix as evidenced by increased collagenolysis and catabolism of glycoconjugates of amorphous connective tissue of the liver. The use of the inhibitor of the transcription factor κB in the background of prolonged alcohol intoxication of animals reduced the concentration of GAG by 1.43 times, lowered oxyproline concentration by 1.6 times and decreased the concentration of sialic acids by 1.14 times compared to chronic alcohol intoxication group. Transcriptional factor NF-κB under conditions of chronic alcohol intoxication affects the architectural remodeling of connective tissue of rat liver by increasing degradation of collagen fibers and destruction of glycoproteins and proteoglycans of the extracellular matrix.
Keywords: liver; alcoholic hepatitis; rats; NF-κB; extracellular matrix